Analysis of smart growth capacity with infill development factors in Maragheh neighborhoods - Freydoun Babaie Aghdam; Hasan Ahar; Hadiseh Gheysari; Farrokh Tahmasebi (نشریه جغرافیا و برنامه‌ریزی, 2017)
In recent decades, cities have grown organically and urban areas in a short time have been several times its original size and city development has been the forms of the individual components, without planning, uncoordinated that urban sprawl pattern is the main feature. Urban Smart Growth cities were developed for deal with problems of sprawl. The case study is Maragheh city. The research method is descriptive and analytical. In this paper, the capacity of Maragheh, using the development from within the main principles of smart growth is about the sprawl, is marked. Indexes such as population density, rate of open space, building quality, access and permeability, compressibility, etc. are used. Neighborhoods with using Analytical Hierarchy presses (AHP) to prioritize and ultimately the level was estimated for each of them. Results show that in 1392 the gross population density of 59.3 persons per hectare is which is considered very low density and On the other hand there is a lot of undeveloped land, 333 hectares, Uses of unconventional urban, and the average per capita level of infrastructure per person is 162.3 square meters. With this description, using the principles of smart growth and in particular, the principle of development from within and Suitable density, Building on wasteland and etc., sprawl can be prevented the sprawl.